Toxicology of Organic Cations and Regulation of Organic Cation Transport in Drosophila melanogaster - Bijelic, George (My University, 2004)
Insects accumulate various xenobiotics and toxic molecules through feeding and environmental exposure. This study examines the toxicology and regulation of a class of toxic molecules, organic cations, in Drosophila melanogaster. The results of this thesis demonstrate that transepithelial tetraethylammonium (TEA) secretion across the main segment of the Malpighian tubules is increased in response to diuretic factors. Both cAMP and cGMP, which increase transepithelial potential (TEP), as well as tyramine and LK-1, which decrease TEP, all enhanced TEA secretion. Both inc~eases and decreases ofTEP may enhance proton transport into the lumen of the tubule thus increasing the rate of organic cation/proton exchange across the apical membrane. These findings suggest that factors previously referred to as diuretic factors may in fact :let primarily or secondarily as stimulants of organic cation excretion. Haemolymrh concentrations of TEA increased linearly with the concentration of TEA in the diet and declined rapidly upon transfer of the larvae to TEA-free diet. The rate of decline was reduced by slowing the metabolic rate or by the addition of cimetidine to a diet containing TEA. Although larvae tolerated high levels of TEA in the diet, mortality increased when TEA was combined with either quinidine or cimetidine. It is suggested that inhibition of TEA transport by cimetidine or quinidine results in prolonged exposure to higher levels of TEA in the haemolymph and a consequent increase in toxicity. Surprisingly, TEA flux and fluid secretion rate were both reduced in Malpighian tubules isolated from adult flies raised on TEA-enriched diet. This suggests that the high concentration of TEA in the diet produced a non-lethal yet deleterious effect on the Malpighian tubules of Drosophila.
Keywords: toxicology; organic cation transport; drosophila melanogaster